ACUTE TUMOR LYSIS SYNDROME ON THE FIRST DAY OF CHEMOTHERAPY IN A PATIENT WITH RELAPSED NON-HODGKIN'S LYMPHOMA - HIDAKA, Takuma; HAMADA, Akira; IKENO, Tsunehisa; OZAWA, Shinji; HASHIMOTO, Isao; FUJITA, Youichi; TSUBOKURA, Hifumi; KITAOH, Takeshi (Japanese Journal of National Medical Services, 2000)
Acute tumor lysis syndrome consists of combinations of hyperuricemia, lactic acidosis, hyperkalemia, hyperphosphatemia, and hypocalcemia, occurrs generally in patient with a high LDH level or renal insufficiency. We reported a 77 year old female with relapsed Non-Hodgkin's lymphoma who developed acute tumor lysis syndrome. Before chemotherapy, multiple lymph nodes were swollew on physical examination and atypical cells were present in peripheral blood. Laboratory data showed normal renal function and LDH level. After starting chemotherapy (ABEP therapy), urine volume was decreased, twenty-four hours later, ECG showed tall T-wave and laboratory data showed hyperkalemia (K 8.1 mEq/l), hyperuricemia (UA18.9 mg/dl) and renal dysfunction (Cr1.9 mg/dl). Acute tumor lysis syndrome is seen less frequently after routine use of allopurinol and hydration. All patients receiving chemotherapy should be closely monitored.